Increasing Moodle resources through cloud computing - Morgado, Eduardo Martins [UNESP] (2012)
The increase of higher education offer is a basic need of developed and emerging countries. It requires increasing and ongoing investments. The offer of higher education, by means of Distance Learning, based on the Internet, is one of the most efficient manners for the massification of this offer, as it allows ample coverage and lower costs. In this scenario, we highlight Moodle, an open and low-cost environment for Distance Learning. Its utilization may be amplified through the adoption of an emerging Information and Communication Technology (ICT), Cloud Computing, which allows the virtualization of Moodle sites, cutting costs, facilitating management and increasing its service capacity. This article diffuses a public tool, opened and free, for automatic conversion of Moodle sites, such that these may be hosted on Azure: the Cloud Computing environment of Microsoft. © 2012 AISTI.